The Influence of Emotional Intelligence and Teacher Workload on Teacher Performance - Annisa Husninadiyah Susanto; Ida Bagus Gede Surya Abadi (Indonesian Journal Of Educational Research and Review, 2021)
There are still many teachers who have not been able to act professionally. Lack of emotional intelligence and motivation of teachers to complete tasks hampers teacher performance. This research was an ex post facto research. The population in the study involved 46 respondents. The techniques used to collect data are observation, interviews, and questionnaires. The instrument used in analyzing the data is a questionnaire. The data analysis method used consists of classical assumption tests and hypothesis testing. Classical assumption test consisted of residual normality test, heteroscedasticity test, multicollinearity test, and SPSS-assisted linearity test. Hypothesis testing used simple linear regression analysis and multiple linear regression analysis assisted by SPSS. The study results based on simple linear regression analysis and multiple linear regression analysis showed that (1) there was no effect of emotional intelligence on teacher performance. (2) There was an effect of workload on teacher performance with a contribution of 98%. (3) There is an influence of emotional intelligence and teacher workload on teacher performance with a contribution of 14.3%. It can be concluded that there is an influence of emotional intelligence and teacher workload on the performance of elementary school teachers.